Pengaruh Kepemimpinan Transaksional, Komunikasi dan Beban Kerja Terhadap Turnover intention melalui Kepuasan Kerja Sebagai Variabel Intervening Pada PT XYZ Cabang Palopo - Sugiarto; Moh Hatta; Novita Rosanti (Jurnal Online Manajemen ELPEI, 2026)
The purpose of this study was to analyze the influence of transactional leadership, communication, and workload on job satisfaction and their implications for turnover intention among Account Officers (AO) at PT XYZ Palopo Branch. The sample in this study consisted of all Account Officers at PT XYZ Palopo Branch, with a total of 194 respondents. The analytical methods used in this study were smart PLS testing, descriptive analysis, and hypothesis testing. The results of the study indicate that: (1) Transactional leadership has a negative but insignificant effect on turnover intention; (2) Transactional leadership has a positive but insignificant effect on job satisfaction; (3) Communication has a positive but insignificant effect on turnover intention; (4) Communication has a positive and significant effect on job satisfaction; (5) Workload has a positive and significant effect on turnover intention; (6) Workload has a negative but insignificant effect on job satisfaction; (7) Job satisfaction has a negative and significant effect on turnover intention; (8) Job satisfaction does not mediate the effect of workload on turnover intention; (9) Job satisfaction does not mediate the effect of transactional leadership on turnover intention; and (10) Job satisfaction significantly mediates the effect of communication on turnover intention in a negative direction.